2006
DOI: 10.1002/masy.200690110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Triblock Terpolymers with three Potentially Crystallisable Blocks: Polyethylene‐b‐poly(ethylene oxide)‐b‐poly(ε‐caprolactone)

Abstract: Summary: A first attempt was made to produce novel ABC triblock terpolymers with three potentially crystallisable blocks: polyethylene (PE), poly(ethylene oxide) (PEO), and poly(e-caprolactone) (PCL). Polybutadiene-b-poly(ethylene oxide) diblock copolymers were synthesized by living anionic polymerization. Then, a non-catalyzed thermal polymerization of e-caprolactone from the hydroxyl end group of the PB-b-PEO diblock precursors was performed. Finally, hydrogenation by Wilkinson catalyst produced PE-b-PEO-b-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Ohno and coworkers investigated dicationic PEG‐based molten salts bearing imidazolium cations as ion conducting materials 40. Basically, modified PEO‐polymers can be prepared via anionic polymerization, based on methods developed earlier (for relevant citaitons see refs 41–44…”
Section: Introductionmentioning
confidence: 99%
“…Ohno and coworkers investigated dicationic PEG‐based molten salts bearing imidazolium cations as ion conducting materials 40. Basically, modified PEO‐polymers can be prepared via anionic polymerization, based on methods developed earlier (for relevant citaitons see refs 41–44…”
Section: Introductionmentioning
confidence: 99%
“…Some of us, synthesized a PE-b-PEO-b-PCL triblock terpolymer in which the central block was not able to crystallize, mainly due to topological restrictions imposed by the previously crystallized PE and PCL blocks. 11 Later, Sun et al reported the synthesis of triblock and pentablock terpolymers composed of PCL, PLLA and PEG. 12 The authors reported that the terpolymers were crystalline from DSC analysis and WAXS experiments performed at room temperature.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The second type is polyethylene‐ block ‐poly(ethylene oxide)‐ block ‐poly( ε ‐caprolactone) (PE‐ b ‐PEO‐ b ‐PCL), which was reported by Abetz and his coworker in 2006 . To the best of our knowledge, this is the only example of tricrystalline triblock terpolymer containing PE block in the chain due to the challenging polymerization steps.…”
Section: Introductionmentioning
confidence: 85%